Finite Element Analysis of 2205 Duplex Stainless Steel Welds - Kisasoz, Alptekin; Karaaslan, Ahmet (CARL HANSER VERLAG, 2014)
Duplex stainless steels are sensitive to high temperature exposure. The microstructure of the duplex stainless steels changes at high process temperatures. Such microstructural changes might affect the mechanical properties and corrosion resistance of duplex stainless steel. Therefore, the microstructural properties of 2205 duplex stainless steel welds were studied and respective microstructural changes during the welding process have been investigated by finite element analysis before fabrication process. 2205 duplex stainless steels were welded using the TIG process. The heat distribution along the cross section of weldments according to the TIG welding parameters was calculated by finite element analysis using ANSYS software. After metallographic preparation of the weldments, each sample was etched by electro-chemical method and the ferrite-austenite ratio was examined by light microscopy. The finite element analyses and microscopic results were compared and the mechanical properties of the weldments were investigated using hardness tests.
Keywords: Materials testing; duplex stainless steel; welding; finite element analysis; AUSTENITE; Materials Science